ANALYZING THE IMPACT OF STEM CHALLENGES ON 21ST CENTURY SKILLS IN PRIMARY GRADE STUDENTS IN CONTEXT OF PAKISTAN - Tasneem Saifuddin; Shairoz Anis; Neelum Siddiqui; Maria Khan; Sonia Ishrat (International Journal of Contemporary Issues in Social Sciences, 2024)
ABSTRACT The aim of the current study is to find out the impact of STEM challenges on the 21st century learning skills on primary grade students in an elite school of Pakistan. STEM challenges proved to be the one of the leading approaches now a days to develop 21st century skills among students (Nadelson and Seifert, 2017). Many elite schools in our context are currently utilizing learner centered pedagogies to develop critical thinking and problem-solving skills in students. The study was designed to find out the integration of STEM challenges into the curriculum to find out its effectiveness in developing 21st century skills among students. Action Research was designed for the study, data being collected in form of scores on adapted rubrics and analysis was done on SPSS version 23. Analysis revealed that the school is already integrating STEM challenges likely produce significant effect on development of 21st century skills. The study also revealed the gender equality in learning STEM challenges as results showed no significant differences in development of 21st century skills among male and female students, both performed equally well. The study also directed future researchers to explore the efficacy of STEM Challenges in government schools.